Network Analysis of Medical Claims Data Suggests Network-Based, Regional Targeting and Intervention Delivery Strategies to Increase Access to Office Based Opioid Treatment (OBOT) for Opioid Use Disorder (OUD) - Harold D. Green PhD; Patrick C. Kaminski MA (SAGE Publishing, 2024)
Opioid overdose and Opioid Use Disorder (OUD) statistics underscore an urgent need to significantly expand access to evidence-based OUD treatment. Office Based Opioid Treatment (OBOT) has proven effective for treating OUD. However, limited access to these treatments persists. Recognizing the need for significant investment in clinical, behavioral, and translational research, the Indiana State Department of Health and Indiana University embarked on a research initiative supported by the "Responding to the Addictions Crisis" Grand Challenge Program. This brief presents recommendations based on existing research and our own analyses of medical claims data in Indiana, where opioid misuse is high and treatment access is limited. The recommendations cover target providers, intervention focus, priority regions, and delivery methods.